Pemanfaatan Cyberlink PowerDirector Pada Pembelajaran Menulis Teks Laporan Hasil Observasi (Utilization of Cyberlink PowerDirector in Learning to Write Text Observation Reports) - Ika Mustika; Ryan Dwi Puspita; Duhita Savira Wardani; Aji Satrio (Indonesian Language Education and Literature, 2023)
This study aims to develop a Flipped Classroom learning model assisted by the Cyberlink PowerDirector application in learning to write Observation Reports (LHO) texts. This type of research is research & development (R&D) which modifies the 10-step Dick & Carey model into 7 stages. The instruments used in this study were validation sheets, questionnaires, observation sheets, and observation report format sheets. A limited try-out was conducted on class VII students of SMPN 16 Cimahi and a wide try-out was carried out on class VII students of SMP Al-Amin Cimahi. The sample used was 90 students from class VII. The data analysis technique used is qualitative and quantitative data analysis techniques. The results of the study show that the mean score of material and media validation is in the very valid category. There is a difference in the average post-test results of the experimental and control classes.Penelitian ini bertujuan untuk mengembangkan model pembelajaran Flipped Classroom berbantuan aplikasi Cyberlink Powerdirector dalam pembelajaran menulis teks Laporan Hasil Observasi (LHO). Jenis penelitian ini adalah penelitian & pengembangan (R&D) yang memodifikasi 10 langkah model Dick & Carey menjadi 7 tahapan. Instrumen yang digunakan dalam penelitian ini yaitu lembar validasi, angket, lembar observasi, dan lembar format laporan hasil observasi. Uji coba terbatas dilakukan pada siswa kelas VII SMPN 16 Cimahi dan uji coba luas dilakukan pada siswa kelas VII SMP Al-Amin Cimahi. Sampel yang digunakan 90 siswa kelas VII.Â Teknik analisis data yang digunakan yaitu teknik analisis data kualitatif dan kuantitatif. Hasil penelitian menunjukkan bahwa hasil rerata skor validasi materi dan media berada pada kategori sangat valid. Terdapat perbedaan rerataÂ hasil posttest kelas eksperimen dan kontrol